Explaining Informal Policy-Making Patterns in the Eurozone Crisis: Decentralized Bargaining and the Theory of EU Institutions. Issue 14 (6th December 2017) - Schoeller, Magnus; Guidi, Mattia; Karagiannis, Yannis
ABSTRACT: During the Eurozone crisis, the so-called 'Merkozy duumvirate' emerged as an informal, but highly visible EU policy-making pattern. This article asks why such forms of decentralized bargaining emerge and what this implies for the theory of EU institutions. According to an approach based on negotiation theory, the article argues that Merkozy is a strategic tool used by Germany to realize its preferences on EU crisis management. Based on an incomplete contracts theory of EU institutions, instead, the article analyses Merkozy as an informal institution created by France and Germany to avoid being discriminated by supranational institutions. Both approaches are employed to assess Merkozy's role in the decision-making process leading to the adoption of the Fiscal Compact.